3x-6+3x-6+2x+2+2x+2=142

Simple and best practice solution for 3x-6+3x-6+2x+2+2x+2=142 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-6+3x-6+2x+2+2x+2=142 equation:


Simplifying
3x + -6 + 3x + -6 + 2x + 2 + 2x + 2 = 142

Reorder the terms:
-6 + -6 + 2 + 2 + 3x + 3x + 2x + 2x = 142

Combine like terms: -6 + -6 = -12
-12 + 2 + 2 + 3x + 3x + 2x + 2x = 142

Combine like terms: -12 + 2 = -10
-10 + 2 + 3x + 3x + 2x + 2x = 142

Combine like terms: -10 + 2 = -8
-8 + 3x + 3x + 2x + 2x = 142

Combine like terms: 3x + 3x = 6x
-8 + 6x + 2x + 2x = 142

Combine like terms: 6x + 2x = 8x
-8 + 8x + 2x = 142

Combine like terms: 8x + 2x = 10x
-8 + 10x = 142

Solving
-8 + 10x = 142

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + 10x = 142 + 8

Combine like terms: -8 + 8 = 0
0 + 10x = 142 + 8
10x = 142 + 8

Combine like terms: 142 + 8 = 150
10x = 150

Divide each side by '10'.
x = 15

Simplifying
x = 15

See similar equations:

| 7x+14=42 | | (130-x)+x=130 | | -6x+x=-2-6(-12x-13) | | (20÷4*2÷5-1)/(-9(-3)-12÷3) | | x^2-43560=0 | | 17j-9j-7j=13 | | m^2+26m-37=0 | | 7c+4c+5c-15c=8 | | 3x+6+2x+4+4x-2=126 | | 20x+13=21x+9 | | p^2-10p-39=0 | | 7s-5s-s=9 | | 4d+7=3d+15 | | C(4,1)*(5/25)*(20/25)^3 | | -3x^2+2xy=0 | | 8p-7p=17 | | x^3-6y^2-9y^1=0 | | 2.5-2.5x=-3 | | 2x+7-3=-8+x+7+2x | | 6cos^2x=3+3sinx | | 10j-4j=18 | | 12+7x=2(x+6)+5x | | 3(x-3)=-0.6 | | 8y-2x=2x-y | | 1.6n-72=4n-30 | | ((9ab^3)^(1/2))/((ab)^(1/2)) | | 5(a+5)=64.5 | | 12(2x+2)=60 | | 16-2y=22 | | 2y+3x=310 | | 19t-17t=16 | | 3y+2x=310 |

Equations solver categories